A clinical comparative study of multiple sclerosis and neuro-Behçet's syndrome. Issue 3 (March 1980) - Motomura, S; Tabira, T; Kuroiwa, Y
Abstract : Clinical comparisons were made between Japanese patients with multiple sclerosis (66 cases) and neuro-Behçet's syndrome (23 cases). Those with neuro-Behçet showed marked male predominance, while those with multiple sclerosis showed slight female preponderance. Both showed encephalomyelopathy disseminated in time and space. Patients with multiple sclerosis, however, showed a more polyphasic course, whilst those with neuro-Behçet showed a more progressive one. In multiple sclerosis optic neuritis, acute transverse myelitis, painful tonic seizures, mental disturbance and internuclear ophthalmoplegia were common. On the other hand, in neuro-Behçet the main neurological manifestation was progressive pseudobulbar palsy. Serum and CSF showed more inflammatory changes in neuro-Behçet than in multiple sclerosis. Clinical estimation suggested that in multiple sclerosis the main lesions were in the optic nerve, tegmentum of the brain stem and spinal cord, whereas in neuro-Behçet they were in the basal parts of the brain stem.